2014
DOI: 10.1080/15614263.2014.958488
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic effects in policing: perceptions, stigmas and help seeking behaviours

Abstract: This study explored the relationships between perceptions, stigmas and support with help seeking amongst police officers. A total of 421 web surveys were completed by constables from a large municipal police force in Canada. The most significant finding was the relationship between officers feeling comfortable disclosing distressing personal information and seeking help from others. Help was most commonly sought from respondents' friends (at work and outside) and family members. Respondents shared information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
37
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 70 publications
5
37
2
Order By: Relevance
“…Because police officers are typically regarded as self-reliant, tough and aggressive (Soomro and Yanos 2018), any display of emotional response to work stressors will risk them being stigmatised for appearing weak (Kurtz 2008). Any vulnerability may cause colleagues to distrust their ability (Heffren and Hausdorf 2016). This negative mindset from colleagues and line management leads to the individual feeling uncomfortable in sharing any psychological suffering for fear of the repercussions, resulting in many continuing to suffer in silence, thus preventing early psychological intervention (Garbarino et al 2013).…”
Section: Subtheme 12: Emotional Response Is a Sign Of Weaknessmentioning
confidence: 99%
See 2 more Smart Citations
“…Because police officers are typically regarded as self-reliant, tough and aggressive (Soomro and Yanos 2018), any display of emotional response to work stressors will risk them being stigmatised for appearing weak (Kurtz 2008). Any vulnerability may cause colleagues to distrust their ability (Heffren and Hausdorf 2016). This negative mindset from colleagues and line management leads to the individual feeling uncomfortable in sharing any psychological suffering for fear of the repercussions, resulting in many continuing to suffer in silence, thus preventing early psychological intervention (Garbarino et al 2013).…”
Section: Subtheme 12: Emotional Response Is a Sign Of Weaknessmentioning
confidence: 99%
“…However, there still remains a gap between acknowledging this need and a call to action (Johnson 2016). A willingness to speak with others in a supportive environment is critical in help-seeking behaviour (Heffren and Hausdorf 2016).…”
Section: Subtheme 4: Breaking Down Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…LEOs are routinely exposed to trauma in a myriad of ways, including the witnessing of the aftermath of interpersonal violence, motor vehicle accidents, child abuse, the possibility of having to be the initiator of violence in life‐threatening situations, such as an officer‐related shooting, as well as homicide and suicide. One study confirmed that most police officers (76%) are exposed to major traumatic events other than suicide, with one third reporting the trauma exposure was personally traumatic for them (Heffren & Hausdorf, ). LEOs acknowledge the importance of trauma on their colleagues, with one study finding over half of the participants having personally known LEO who “changed” after experiencing a traumatic event (Fleischmann, Strode, Broussard, & Compton, ).…”
mentioning
confidence: 99%
“…For example, police officers who experienced a traumatic event reported a higher percentage of suicidal thoughts (27.2%) when compared to those who did not report experiencing a traumatic event (7.7%) (Fleischmann et al., ). Despite these research findings, many LEOs do not acknowledge the trauma to which they are exposed, or attempt to deal with it on their own (Heffren & Hausdorf, ).…”
mentioning
confidence: 99%